Sacred Sites, Cultural Insights: Exploring Spiritual Tourism in Bharat - Dr. Rajeshwari Jain, Dr. Preyal Sanghvi, Khushboo Vachhani Talati, Dr. Jiju Mathew John (South Eastern European Journal of Public Health, 2025)
A survey of 400 respondents across Gujarat was conducted to explore their experiences and perceptions regarding spiritual tourism in Bharat. The survey examined respondents' familiarity with spiritual tourism destinations and whether they believed spiritual tourism had positive economic effects on local communities. It also sought to understand respondents' awareness of the cultural implications of the rapidly growing spiritual tourism industry in Bharat. Statistical analysis and factor analysis have been done. Results classified respondents into three categories: 'The Conscious Spiritual Traveler,’ ‘The Wellness-Seeking Traveler’, and, ‘The Culturally Immersive Traveler’ investigating how spiritual tourism can drive global interest in Bharat’s cultural heritage by analysing travellers’ motivations, beliefs, and the emotional value of spiritual destinations. Findings highlight the need for better promotion of Bharat’s spiritual sites to attract global tourists and enhance the tourism industry's potential. Effective marketing strategies that appeal to Gen Z, promoting increased cultural awareness, and improving accessibility to spiritual sites, along with supportive government policies, contribute to the growth and documentation of Bharat's cultural heritage and tourism.